Social Context Influence on Urban Gardener Perceptions of Pests and Management Practices - Liere, Heidi; Egerer, Monika; Sanchez, Carly; Bichier, Peter; Philpott, Stacy M. (Frontiers in Sustainable Food Systems, 2020)
Community gardens are important urban green spaces with a variety of social and ecological benefits, one of which is access to healthy food. Similar to rural agriculture, the quantity and quality of the food produced can be compromised by pest damage. In fact, many urban gardeners report crop damages caused by vertebrate and invertebrate pests. Yet, because the food produced in community gardens is mostly for self-consumption and thus not under market quality standards, the damage thresholds and the point when gardeners perceive a pest problem and how they decide to manage it, may greatly vary from gardener to gardener. Here, we investigated how socio-demographic factors and experience affect whether gardeners report having a pest problem and which pest management practices they use. We surveyed 187 gardeners from 18 different urban community gardens in three counties in the California central coast, USA. We also collected information about gardener socio-demographic factors (age, gender, ethnicity), as well as education, and years of experience in agriculture. The majority of gardeners reported having pests in their plots but their ethnicity, the amount of time they spend in the gardens, and whether they work in agricultural-related employment or not influenced the likelihood of reporting pests. We found that the majority of gardeners use curative, non-synthetic practices for managing pests, but that some use preventive practices and some don’t do anything to control pests. The likelihood of using practices that are curative depended on gardeners’ ethnicity, the amount of time they spend in the gardeners, and their gender. Our results suggest that the agricultural knowledge of urban community gardeners and the practices they use varies greatly and that, in order to be successful, extension programs may need to take this diversity into account when promoting the agroecological paradigm in urban agricultural systems.